Assessment of visual comfort in the lighting environments of subway cabins in China. Issue 3 (4th May 2023) - Xu, Jian; Xiang, Ze-Rui; Zhi, Jin-Yi; Chen, Yao-Dong; Xu, Xiao-Fei
ABSTRACT: This paper presents a multi-dimensional evaluation and comparison of the visual comfort of the cabin lighting environments of five subways lines in Chengdu. The study proposes a visual comfort evaluation procedure that integrates objective and subjective methods combined with existing visual comfort measurement methods. Based on this evaluation procedure, the lighting conditions (illuminance and glare) in each cabin were measured using an illuminance metre and high-dynamic image technology, and an online questionnaire was used to understand passengers' subjective experiences of cabin lighting. The results show that: seating layout has no significant influence on the visual performance of mobile phones or on spatial brightness; horizontal illuminance in the lighting environments of subway cabins has no significant influence on task performance of passengers using mobile phones; the overall perception of subway cabin spatial brightness increases with vertical illuminance; and passengers have no obvious preference for a cabin correlated colour temperature.